REPORTING OF BLIC AND POLITIKA ABOUT BREXIT: THE PRESENCE OF IDENTITY-FOR-OTHER IN THE MEDIA DISCOURSE IN SERBIA - Milinkov, Smiljana; Šinković, Norbert (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
This paper presents the analysis of the scope and manner of media reporting about the referendum on the status of Great Britain in the European Union, which was held on 23 June 2016. Empirical research was conducted using quantitative and qualitative methods: content analysis and media discourse analysis. The sample includes online editions of two daily newspapers, Politika and Blic, both monitored a week before the scheduled referendum and two days after the referendum. The results of analysis have confirmed previous research of media in Serbia which showed that media coverage of the European Union is superficial, based on coverage of daily political events, predominantly factual and mostly without deeper analysis. The research has shown that the analysed media did not have a clear critical distance from authorities and official politics in general. The analysis of media coverage of UK leaving the European Union has showed the presence of dominant ‘identity-for-other’ in media discourse in Serbia, which is in the case of Brexit by the impact of the East (Russia) and the West (Europe and USA).